1992
DOI: 10.1192/pb.16.5.264
|View full text |Cite
|
Sign up to set email alerts
|

Changes in referral rates following community psychiatric nurse attachment to a primary care team

Abstract: Over the past three decades there has been a shift in emphasis from hospital based to community care of psychiatric patients. Central to this change has been the development of the community psychiatric nursing services and an increase in its numbers. Until recently community psychiatric nurses (CPNs) were almost entirely hospital based, working as members of a multidisciplinary team and providing follow-up for psychiatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…The opportunity for community mental health nurses to contribute to the developments of mental health care in primary care is one that needs to be taken so that understanding can be gained as to how they might function in this context, how they might engage with clients and other members of the primary care team, and the types of interventions they might provide (Hannigan 1997). While there has been an increasing focus on GP perceptions of CMHNs (Stansfeld et al 1992, Wells et al 1992, Kendrick et al 1993, Warner et al 1993, Monkley‐Poole 1995, Corney 1996, Hannigan et al 1997, Badger & Nolan 1999), there are few, if any, studies which examine the perceptions of all PHCT members (Badger & Nolan 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The opportunity for community mental health nurses to contribute to the developments of mental health care in primary care is one that needs to be taken so that understanding can be gained as to how they might function in this context, how they might engage with clients and other members of the primary care team, and the types of interventions they might provide (Hannigan 1997). While there has been an increasing focus on GP perceptions of CMHNs (Stansfeld et al 1992, Wells et al 1992, Kendrick et al 1993, Warner et al 1993, Monkley‐Poole 1995, Corney 1996, Hannigan et al 1997, Badger & Nolan 1999), there are few, if any, studies which examine the perceptions of all PHCT members (Badger & Nolan 1999).…”
Section: Introductionmentioning
confidence: 99%
“…However, Gournay & Brooking (1994) demonstrated little evidence for the effectiveness of the interventions of CPNs with nonpsychotic patients and concluded that CPNs were not cost effective in primary care settings and should be directed to manage those with serious mental illnesses. However, a number of studies, including Wells et al (1992) ; and Kendrick et al (1993) found that GPs valued the contribution of CPNs in reducing the number of referrals to psychiatrists, although there was great disparity amongst them about what exactly the role of the CPN should be.…”
Section: Literaturementioning
confidence: 99%
“…The Grampian Psychiatric Case Register, which recorded all referrals to the psychiatric services in Aberdeen, was used to investigate changes in referral rates following community psychiatric nurse (CPN) attachment to a primary care team (Wells et al, 1992). This study was able to use case register data for the two-year period before the CPN attachment and compare this with the three years after the attachment, and demonstrated that referrals to hospital services may be reduced by CPN involvement in primary care.…”
Section: What Can Case Registers Do?mentioning
confidence: 99%